Anthropometric profile of gymnast from childhood to maturity sport: report of 2 cases - Canda, A. S. (Archivos de medicina del deporte, 2016)
Introduction: The aim of the present study was to establish longitudinal anthropometric profile of two gymnasts from infantile category to senior category, and determining the effects of both growth and maturation as well as of high intensity training.